Measurable Residual Disease Detected by Multiparameter Flow Cytometry and Sequencing Improves Prediction of Relapse and Survival in Acute Myeloid Leukemia - Liu, Fu-Jia; Cheng, Wen-Yan; Lin, Xiao-Jing; Wang, Shi-Yang; Jiang, Tian-Yi; Ma, Ting-Ting; Zhu, Yong-Mei; Shen, Yang (Frontiers in Oncology, 2021)
The clinically ideal time point and optimal approach for the assessment of measurable residual disease (MRD) in patients with acute myeloid leukemia (AML) are still inconclusive. We investigated the clinical value of multiparameter flow cytometry-based MRD (MFC MRD) after induction (n=492) and 2 cycles of consolidation (n=421). The latter time point was proved as a superior indicator with independent prognostic significance for both relapse-free survival (RFS, HR=3.635, 95% CI: 2.433-5.431, P<0.001) and overall survival (OS: HR=3.511, 95% CI: 2.191-5.626, P<0.001). Furthermore, several representative molecular MRD markers were compared with the MFC MRD. Both approaches can establish prognostic value in patients with NPM1 mutations, and FLT3, C-KIT, or N-RAS mutations involved in kinase-related signaling pathways, while the combination of both techniques further refined the risk stratification. The detection of RUNX1-RUNX1T1 fusion transcripts achieved a considerable net reclassification improvement in predicting the prognosis. Conversely, for patients with biallelic CEBPA or DNMT3A mutations, only the MFC method was recommended due to the poor prognostic discriminability in tracking mutant transcripts. In conclusion, this study demonstrated that the MFC MRD after 2 consolidation cycles independently predicted clinical outcomes, and the integration of MFC and molecular MRD should depend on different types of AML-related genetic lesions.